Family Education on the Quality of Children in the Covid-19 Era - Khairunnisa Ulfadhilah (JOYCED: Journal of Early Childhood Education, 2021)
The first education for children from an early age is that of the parents. This study aims to describe the role of family education that will affect the quality of children through parenting and parenting. This study used a qualitative approach with a descriptive method to obtain information related to family education about children's calories. Children's calories need to be supervised by parents to determine whether or not the child's nutrition intake is sufficient to fulfill nutrition in children so as not to excess calories in early childhood. Data collection techniques using observation, interviews, and documentation. The results showed that parents assisted children by guiding children in learning and doing assignments from educators, a series of habituation models in speech and behavior.